Short term response of plankton community to nutrient enrichment in central eastern Arabian Sea: Elucidation through mesocosm experiments. (15th June 2021) - Anil, A.C.; Desai, D.V.; Khandeparker, L.; Krishnamurthy, V.; Mapari, K.; Mitbavkar, S.; Patil, J.S.; Sarma, V.V.S.S.; Sawant, S.S.
Abstract: Oligotrophic waters (OW), generally favour longer food chain facilitated by the microbial loop. In such ecosystems, physical mixing (e.g. upwelling, and winter convection) inject nutrients and propagules from subsurface to the photic zone. Such events are expected to alter the food chain through shifts in the plankton community. Mesocosm experiments were carried out to evaluate the influence of nutrient enrichment from the deep (100–150 m) on the surface plankton community for the first time in the Arabian Sea, through custom-designed enclosures in OW of the central-eastern Arabian Sea (CEAS). Surface water was characterized by low nutrients and phytoplankton biomass (chlorophyll-a of <0.2 μg m −3 ) and upon nutrient enrichment yielded differing response. Higher abundance of picophytoplankton, bacteria and protists was noticed at a depth of 100 m than at surface. The inoculation of such a population to the surface, resulted in a significant enhancement of autotrophic (picophytoplankton) and heterotrophic (bacteria and protists) populations. However, significant changes in the abundance of larger plankton was not evident till three days of incubation. Even though autotrophic picophytoplankton responded positively, a distinct increase in chlorophyll-a was not evident. This study points out that the lack of sufficient viable microphytoplankton propagules, neither at the surface nor at the depth (inoculum) are the possible reasons for the lack of their distinct positive response. These experiments suggest the dominance of microbial community response to physical mixing in the OW regions of the Arabian Sea and the importance of propagule diversity. The insights from this experiment will serve as a precursor for appropriate modifications in ocean modelling and forecasting studies and help in building global environmental management tools. Highlights: First free floating mesocosm experiments in the Arabian Sea. In situ evaluation of nutrient enrichment (NE) on oceanic plankton community. Nutrient enrichment triggered microbial (picoplankton & protist) response. Micro phytoplankton & zooplankton response not evident within 3 days of NE. Biological response to NE depends on viable propagule density & incubation period.